An Upper Bound Estimate for H. Alzer’s Integral Inequality - Yuming, Chu; Xiaoming, Zhang; Xiaomin, Tang (Sarajevo Journal of Mathematics, 2024)
We get an upper bound estimate for H. Alzer's integral inequality. As applications, we obtain some inequalities for the logarithmic mean. 2000 Mathematics Subject Classification. 26D07